Vitamin D deficiency in Hashimoto’s thyroiditis: mechanisms, immune modulation, and therapeutic implications - Sun, Wencong; Ding, Chao; Wang, Yichen; Li, Guoqing; Su, Zijie; Wang, Xinhui (Frontiers in Endocrinology, 2025)
BackgroundTo evaluate vitamin D’s role in thyroid autoimmunity modulation, establish evidence-based supplementation protocols, and address surgical implications in Hashimoto’s thyroiditis (HT) care. Vitamin D deficiency is prevalent in HT patients and correlates with accelerated autoimmune progression. This review synthesizes mechanistic insights and clinical implications of vitamin D repletion in HT management.ObjectiveTo evaluate vitamin D’s role in thyroid autoimmunity modulation, establish evidence-based supplementation protocols, and address surgical implications in HT care.Key FindingsPathogenic Mechanism: Vitamin D deficiency (25(OH)D <20 ng/mL) disrupts VDR-mediated Treg/Th17 balance, increasing anti-TPO titers by 40–60% and hypothyroidism progression risk. Therapeutic Window: Supplementation (2000–4000 IU/day) reduces antibodies by 15–30% only in euthyroid TPOAb+ patients with baseline deficiency (<20 ng/mL), but efficacy diminishes in overt hypothyroidism. Surgical Imperative: Preoperative optimization (25(OH)D >30 ng/mL) lowers post-thyroidectomy hypocalcemia risk by 50% in HT patients.ConclusionVitamin D modulates HT through immune pathway regulation, yet response heterogeneity necessitates: Genotype-guided dosing (VDR-FokI FF carriers require 30% lower doses). Vitamin D supplementation has demonstrated potential to modulate immune responses, alleviate symptoms, and improve quality of life.